Lithium and beryllium in the Gaia-Enceladus galaxy. Issue 3 (16th June 2020) - Molaro, P; Cescutti, G; Fu, X
ABSTRACT: Data from Gaia DR2 and The Apache Point Observatory Galactic Evolution Experiment surveys revealed a relatively new component in the inner Galactic halo, which is likely the dynamical remnant of a disrupted dwarf galaxy named Gaia-Enceladus that collided with the Milky Way about 10 Gyr ago. This merging event offers an extraordinary opportunity to study chemical abundances of elements in a dwarf galaxy, since they are generally hampered in external galaxies. Here, we focus on 7 Li and 9 Be in dwarf stars that are out of reach even in Local Group galaxies. Searching in GALAH, Gaia-ESO survey and in literature, we found several existing 7 Li abundance determinations of stars belonging to the Gaia-Enceladus galaxy. The 7 Li abundances of stars at the low metallicity end overlap with those of the Galactic halo. These are effective extragalactic 7 Li measurements, which suggest that the 7 Li Spite plateau is universal, as is the cosmological 7 Li problem. We found a 7 Li-rich giant out of 101 stars, which suggests a small percentage similar to that of the Milky Way. We also collect 9 Be abundance for a subsample of 25 Gaia-Enceladus stars from literature. Their abundances share the Galactic [Be/H] values at the low metallicity end but grow slower with [Fe/H] and show a reduced dispersion. This suggests that the scatter observed in the Milky Way could reflect the different 9 Be evolution patterns of different stellar components that are mixed-up in the Galactic halo.